ANALYSIS OF ECONOMIC PERFORMANCE AND ECONOMIC POTENTIAL OF EAST JAVA PROVINCE - Ahmad Rizani (East Java Economic Journal, 2017)
This study aimed to investigate economic growth, regional economic pattern and structure of East Java Province. Other than that, this study also identified anddetermined superior sectors in East Java Province to give an illustration on which superior economic activities to be developed to improve the economic potential in East Java Province. Data employed in this study was secondary data in six years’ time series form 2010 until 2015 about GDP (Gross Domestic Product) for Indonesia, RGDP (Regional Gross Domestic Product) for East Java Province, total population in Indonesia, total population in East Java Province, the number of people living in poverty in Indonesia, and the number of people living in poverty in East Java Province. Data was obtained from Central Statistics Institution Indonesia, National Planning and Development Institution, Central Statistics Institution of East Java Province, and Regional Planning and Development Institution of East Java Province. Analysis tools used in this study included economic performance analysis, ShiftShare, Location Quotient (LQ), Growth Ratio Model (MRP) and Overlay analysis. The results of the study showed that: (1) economic performance index of East Java Province was quite good because during 2011-2015 the province got average economic performance index 0.847; (2) shift-share analysis showed that East Java Province economic showed an improvement during 2010-2015 by 340.769,50 billion rupiahs. Those economic performance improvements in East Java Province could be seen from the positive value of 16 (sixteen) economic activity sectors; (3) according to Location Quotient (LQ) analysis, there were five superior sectors in East Java Province, they were processing industry sector, water procurement sector, waste and recycle management sector, wholesale and retail, auto car and motorcycle reparation sector, accommodation and foods providing sector, and information and communication sector; (4) Growth Ratio Model analysis showed that sectors which had dominants growth and big contribution were construction sector, wholesale and retail, auto car and motorcycle reparation sector, transportation and warehousing sector, accommodation and foods providing sector, information and communication sector financial and insurance service sector, real estate sector, education service sector, health service and social activity sector; (5) Overlay analysis showed that potential economic sector in East Java Province included wholesale and retail, auto car andmotorcycle reparation sector, accommodation and foods providing sector, and information and communication sector; (6) weighing result according to Shift-Share Location Quotient (LQ), and Growth Ratio Model analysis were five sectors based on the highest rank of the most potential weighing result, they were accommodation and foods providing sector, processing industry sector, wholesale and retail, auto car and motorcycle reparation sector, information and communication sector, and construction sector. JEL Classification : P47, O47, C02, C02, C02, C02